The Utilization of Digital Diplomacy of Non-State Actors: Case Study of The United Liberation Movement for West Papua (ULMWP) - Sagala, Dina Militia Cristy; Baskoro, Riski M. (Jurnal Studi Diplomasi dan Keamanan, 2023)
As one of the provinces that has abundant natural wealth, ironically Papua has various kinds of problems such as the lack of health and education facilities and infrastructure. According to Viartasiwi, these things are one of the main factors behind the emergence of the Papua and West Papua separatist movements. There are several Papua and West Papua separatist movements with various methods and ideologies they adhere to such as OPM, NRFPB, KNPB, and ULMWP. The ULMWP or the United Liberation Movement for West Papua is one of the biggest non-violent movements of the Papuans separatist movement. The group tried to raise the issue of Papua towards the international society to gain support for the independence of West Papua. On the effort to achieve their goal, the ULMWP utilized digital platforms such as creating their own website domains and campaigns from the Twitter accounts of their so called “diplomats” and Spokesperson. This research aimed to discover on how the concept of digital diplomacy can be applied to analyze the phenomenon of the utilization of the digital platform by the ULMWP to achieve their goal. To answer this question, this study will use qualitative research methods by conducting a review of the digital platform used by ULMWP, which from the Twitter accounts of the main ULMWP figures and from their official website, and assisted by the NVivo social media data processing application. This study will use the concept of digital diplomacy by Todorovska which discusses the separatist movement that uses digital diplomacy in achieving its goals. In the final result of this study, it was found that non-state actors such as the ULMWP separatist movement can use digital diplomacy to achieve their goals. With digital diplomacy, the ULMWP can gain international and domestic support, as well as give credence to self-determination aspirations.